Association of Social Media Use with Family Connectedness and Parental Monitoring: A Survey Study of Young Adults in Pakistan - Amina Tariq; Shanchita R. Khan; Oscar Oviedo-Trespalacios; Amna Basharat (Human Behavior and Emerging Technologies)
An increasing number of young adults are using social media platforms in collectivist family cultures like Pakistan, but little is known about how social media use is associated with family connectedness in this population. This study is aimed (a) at examining the social media usage patterns in Pakistani young adults and how they use it to connect with their parents and (b) at exploring the possible association between social media use and perceived family connectedness and parental monitoring. Data came from an online survey conducted among young adults in Pakistan. Patterns of use across various popular social media platforms were recorded. Additionally, family connectedness and parental monitoring were measured. Multiple linear regression analyses were used to examine the relationship between social media used to connect with parents and family connectedness and parental monitoring. A total of 421 participants responded to the survey. All participants regularly used at least two popular social media platforms. WhatsApp was the most used platform irrespective of gender or age, with about 91% of the participants reporting daily usage. Overall, 63% of participants connected with their parents using social media. This varied significantly among male and female participants with 69% of female participants connecting with their parents on social media compared to 59% of males. Connecting with parents on both Facebook and Instagram was highly associated with participants’ perception of parental monitoring before and after adjusting for age and gender. The study highlights that while family connectedness in collectivist societies like Pakistan is not associated with social media usage, adult children perceive parents monitoring their social media activities.